Pengaruh Teknologi Keuangan Terhadap Preferensi Konsumen Memilih Uang Digital Dalam Transaksi Keuangan: Studi Kasus Masyarakat Kota Bukittinggi (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2022)
The purpose of this study is to find out the influence of Financial Technology on people's preferences to choose E-Money as an alternative to facilitate financial transactions in Bukittinggi City. The method used in this study is a quantitative method. The research variable is financial technology (X) as a free variable and consumer preferences choose E-Money (Y) as the bound variable. Sampling with purposive sampling technique with a sample number of 100 respondents. While the data analysis techniques used are simple regression analysis, validity test, reliability test, classical assumption test and hypothesis test. The results of the study data were tested using SPSS IBM 26. Based on the results of research obtained through a simple regression analysis that is Y = 0.755 + 0.55X. The results showed that financial technology had a positive and significant effect on the prefrence of consumers choosing E-Money because thitung 17,564 > 1,660 and significance of 0.000 < 0.05 then H1 received. Based on the research results, it is expected that the community will be able to be adaptive to modern-day developments that are influenced by the industrial revolution 4.0 so that technological changes can make it easier for consumers, not the other way around, on the other hand, support and socialization from regulators (government) and e-money provider institutions must also be improved so that people do not feel burdened by changes to the system that is applied